Implementasi Teori Sosial Kognitif Albert Bandura dalam Pembelajaran Fikih di MI Al Ikhlas Pancawangi - Lilih Parlina (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
The Social Cognitive Theory proposed by Albert Bandura emphasizes that learning occurs largely through the process of observation. Teachers play an important role as models who provide direct examples so that students can understand and imitate a particular action or skill. This study aims to describe the implementation of Albert Bandura's social cognitive theory through modeling strategies in Islamic Jurisprudence learning on the material "Ablution Procedures" in class IA MI Al Ikhlas. This study uses a descriptive qualitative approach with the research subjects being Islamic Jurisprudence subject teachers for class I and 25 class IA students. The research objects include the application of Bandura's modeling theory in Islamic Jurisprudence learning and students' abilities in practicing ablution procedures. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the application of modeling strategies in Islamic Jurisprudence learning consists of three stages, namely: (1) the planning stage, where the teacher prepares a learning plan; (2) the implementation stage, which includes four core processes, namely attention (students pay attention to examples from the teacher), retention (students record information in memory), reproduction (students practice ablution procedures), and motivation (the teacher provides reinforcement in the form of praise or rewards); and (3) the evaluation stage, which is carried out through written, oral and practical tests. The application of this theory has proven effective in improving students' ability to practice ablution correctly.